Amphipols for Each Season - Zoonens, Manuela (J Membr Biol, 2014)
Amphipols (APols) are short amphipathic polymers that can substitute for detergents at the transmembrane surface of membrane proteins (MPs) and, thereby, keep them soluble in detergent-free aqueous solutions. APol-trapped MPs are, as a rule, more stable biochemically than their detergent-solubilized counterparts. APols have proven useful to produce MPs, most noticeably by assisting their folding from the denatured state obtained after solubilizing MP inclusion bodies in either SDS or urea. They facilitate the handling in aqueous solution of fragile MPs for the purpose of proteomics, structural and functional studies, and therapeutics. Because APols can be chemically labeled or functionalized, and they form very stable complexes with MPs, they can also be used to functionalize those indirectly, which opens onto many novel applications. Following a brief recall of the properties of APols and MP/APol complexes, an update is provided of recent progress in these various fields.